‘DEEP-FRIED’ AND DENATURALIZED: CRITIQUING MEMETIC META- ONTOLOGIES - Kowalchuk, Saskia (AoIR Selected Papers of Internet Research, 2018)
In this paper, I have sought to introduce and outline the trend in Internet meme-making know as 'deep-frying' and explain its significance as a method of user critique within a naturalized medium. How do images that confuse and repel the casual viewer through profanity, enthusiastic emoji usage, over-saturation, repeated compression, bubbling/ warping, and excessive lens flaring effectively question the memetic paradigm? Firstly, by understanding memes as Hito Steryl's transgressive 'poor images' that circulate to produce communities of content creators and consumers that stand in opposition to the state-sponsored rich image making complex. Further, through the application of work by Rolande Barthes, Claude Shannon & Warren Weaver, Scott Contreras-Kotterbay & Łukasz Mirocha, and Rosa Menkman, I have produced a critical examination of the formal practices that elucidate this phenomenon, on the level of the linguistic & iconic message, noise level, and redundancy. Lastly, I propose an orientation of these works within a diverse corpus across various major social media as a networked art practice in keeping with the tenants of the New Aesthetic.